Contractual Relationships and Processes of Business Actors in Government Procurement of Construction Goods and Services from a Civil Law Perspective (Discourse Journal on Law and Society, 2025)
The contractual relationship between government entities (PA/KPA/PPK) and construction service providers in procurement activities is complex, as it intersects with both public and private law. Government procurement contracts for construction projects are often structured through a tender process, where service providers must compete to win the contract. Once the provider is selected, a legal agreement is formed, which regulates the roles, responsibilities, and obligations of the parties involved. This agreement is typically outlined in a contract document that serves as a formal, legally binding commitment. In civil law, such contracts are typically governed by private law principles, which include contracts, obligations, and liabilities. However, the nature of government procurement contracts adds a unique element of public law, particularly administrative and criminal law. The government’s involvement in these contracts introduces a dual legal framework that governs the relationship between the parties. On one hand, the contract is influenced by the state’s regulatory powers and administrative authority, ensuring compliance with legal standards and public interests. On the other hand, it is also subject to private law principles, as the government enters into agreements with construction providers just like any other business transaction. This mixed legal framework (or "mixed law") creates a distinctive legal relationship, where elements of public law, such as administrative regulations and oversight, coexist with private law principles, such as those governing contract enforcement and dispute resolution. The contract, which is a Keputusan Tindakan Administrasi Negara (KTUN), remains a civil law act, despite its public law foundation. This hybrid nature of government contracts ensures that both public and private law aspects are considered in the process, which can sometimes lead to legal complexities and challenges in the implementation and enforcement of these contracts.